(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Nagabala -Arjunadi Yoga, is the combination of Nagabala and Arjuna Churna mentioned in Chakradatta, Hridroga Chikitsa, is prepared by giving Bhavana of Rasonadi Kwatha. Hridroga (cardiovascular disorders) are the most common health concern of the present era. It is the leading cause of death worldwide. Ancient Samhitas contain many formulations in the context of Hridroga, whose applicability is unexplored. Churna and Kwatha are the main dosage forms used in clinical practice. But compared to Churna and Kwatha, tablets are more patient compatible in terms of palatability and possess increased shelf life. Hence, Nagabala-Arjunadi Yoga, a tablet dosage form is developed using Nagabala- Arjuna Churna and Rasonadi Kwatha. No scientific evaluation data for this drug is available to date. The present study was done to evaluate the pharmacognostical and pharmaceutical profile of Nagabala-Arjunadi Yoga. The microscopic examination of the Nagabala- Arjunadi Yoga showed the presence of rosette crystals, rhomboidal crystals, simple fibres, oil globules and stones cells. The physicochemical analysis showed that pH value, hardness, loss on drying, ash value, water extractive value and methanol extractive value was 5.8, 3.5kg/cm2, 7.949%, 3.03%, 17.43%, 16.14% respectively. The HPTLC densitograms at UV 254 nm and UV 366nm using Toluene and Ethyl acetate in the ratio 9:1 showed maximum peak height in 3rd peak corresponding to the Rf value 0.18 and 0.17 respectively. The finding observed in the present study can be used as reference for future quality control.